2020
DOI: 10.1021/acsbiomaterials.9b01884
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Early Healing Response to Dicationic Imidazolium-Based Ionic Liquids: A Biocompatible Coating for Titanium Implants

Abstract: Dicationic Imidazolum-based ionic liquids with amino acid anions (IonL) have been proposed as a multifunctional coating for titanium dental implants, as their properties have been shown to address multiple early complicating factors while maintaining host cell compatibility. This study aims to evaluate effects of this coating on host response in the absence of complicating oral factors during the early healing period using a subcutaneous implantation model in the rat. IonLs with the best cytocompatibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 80 publications
2
32
0
Order By: Relevance
“…In the context of this early inflammation and considering the nature of both connective tissues, the subcutaneous model is viable to understand the general features of the inflammatory response and/or FBR to the corroded biomaterial. However, titanium implantation follows a well-orchestrated inflammatory response that ultimately leads to bone apposition in osseointegration model (Davies, 2003;Wheelis et al, 2021), while in connective tissue, it leads to a well-organized capsule with no evidence of FBGC (Biguetti et al, 2019;Wheelis et al, 2020). Thus, the gradual differentiation of bone cells and bone deposition is another sophisticated step that required additional investigation in this study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the context of this early inflammation and considering the nature of both connective tissues, the subcutaneous model is viable to understand the general features of the inflammatory response and/or FBR to the corroded biomaterial. However, titanium implantation follows a well-orchestrated inflammatory response that ultimately leads to bone apposition in osseointegration model (Davies, 2003;Wheelis et al, 2021), while in connective tissue, it leads to a well-organized capsule with no evidence of FBGC (Biguetti et al, 2019;Wheelis et al, 2020). Thus, the gradual differentiation of bone cells and bone deposition is another sophisticated step that required additional investigation in this study.…”
Section: Discussionmentioning
confidence: 95%
“…When Ti is compared with copper, the resulting connective tissue capsule around copper displayed a higher amount of macrophages and FBGC and higher levels of proinflammatory cytokines (Suska et al, 2003). In previous studies, cpTi disk implantation in subcutaneous tissue was followed by a mild and transitory inflammatory response (Biguetti et al, 2019;Wheelis et al, 2020), and a well-tolerated response has also been shown with modified Ti alloys (silver thiolate-modified Ti) (Tîlmaciu et al, 2015). Accordingly, our results from control cpTi groups implanted in subcutaneous tissue demonstrated a constructive and mild inflammation along with gradual deposition and remodeling of the collagenous matrix in subcutaneous tissue, with no evidence of FBGC formation (Figure 3).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…CD68-positive cells were mostly expressed in macrophages and a large amount of macrophages infiltration in the early stage of transplantation would lead to collagen deposition and scar formation. Many studies have shown that reducing macrophage infiltration or regulating macrophage polarization can reduce inflammatory response and promote tissue repair [ 26 ]. On the other hand, we detected more P63 positive cells in the cryopreserved ECSs, which was conducive to epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%